2015
DOI: 10.1182/blood-2014-07-589150
|View full text |Cite
|
Sign up to set email alerts
|

CMV promotes recipient T-cell immunity following reduced-intensity T-cell–depleted HSCT, significantly modulating chimerism status

Abstract: Key Points• CMV serostatus significantly influences chimerism levels after T-cell-depleted allogeneic transplantation.• CMV-specific T cells are exclusively of recipient origin after R1/D2 T-cell-depleted transplants and appear to provide protective immunity.Cytomegalovirus (CMV) remains a significant cause of morbidity after allogeneic hematopoietic stem cell transplantation (HSCT). Clinical risk varies according to a number of factors, including recipient/donor CMV serostatus. Current dogma suggests risk is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
1
29
1
2
Order By: Relevance
“…9 Specifically, subset analysis was performed on 446 adult patients with AML receiving PBSC grafts following a MA conditioning regimen without serotherapy and who received cyclosporine (CSA) and methotrexate (MTX)-based GVHD prophylaxis. In this subset analysis, CMV reactivation as a time-dependent covariate did not associate with decreased risk for relapse by 1 year (CMV reactivation: n 5 113, relapse 26% [95% CI, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] vs no CMV reactivation: n 5 333, relapse 27% [95% CI, 22-32%]; P 5 .80). Likewise, D/R CMV serology itself did not associate with reduced risk for relapse (data not shown).…”
Section: Subset Analysis Focusing On Aml Patients Receiving Pbsc Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Specifically, subset analysis was performed on 446 adult patients with AML receiving PBSC grafts following a MA conditioning regimen without serotherapy and who received cyclosporine (CSA) and methotrexate (MTX)-based GVHD prophylaxis. In this subset analysis, CMV reactivation as a time-dependent covariate did not associate with decreased risk for relapse by 1 year (CMV reactivation: n 5 113, relapse 26% [95% CI, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] vs no CMV reactivation: n 5 333, relapse 27% [95% CI, 22-32%]; P 5 .80). Likewise, D/R CMV serology itself did not associate with reduced risk for relapse (data not shown).…”
Section: Subset Analysis Focusing On Aml Patients Receiving Pbsc Graftsmentioning
confidence: 99%
“…[25][26][27] Ironically, CMV-driven immunity by itself seems not to influence risk in leukemia relapse after HCT, but rather overall immune reconstitution in the allogeneic transplant recipient seems most important. 15 The current CIBMTR study performed a subset analysis on AML patients who received MA conditioning and PBSC grafts, as early CMV reactivation in this specific patient population has most often been reported to decrease AML relapse.…”
Section: Org Frommentioning
confidence: 99%
“…A recent study in recipients of reduced-intensity conditioning HCT with grafts post- in-vivo TCD with alemtuzumab showed that R+/D− patients had fewer CMV related events and higher levels of recipient chimerism than R+/D+ recipients. Furthermore, CMV specific T-cells in R+/D− recipients were exclusively of recipient origin 23 . In our cohort, we also observed that R+/D+ patients had significantly higher CMV reactivation, numerically higher CMV persistent viremia, and worse one-year overall survival outcomes than R+/D− patients.…”
Section: Discussionmentioning
confidence: 99%
“…Нами продемонстрировано, что пациенты со злокаче-ственными заболеваниями имеют более высокий риск реактивации ЦМВ-инфекции по сравнению с пациен-тами с незлокачественными заболеваниями, о чем свидетельствует результат мультивариантного ана-лиза. Этот факт частично объясняют опубликованные сообщения о роли персистирующих ЦМВ-специфиче-ских T-лимфоцитов реципиентов в контроле ЦМВ-ин-фекции после ТГСК [37]. Это предположение косвенно подтверждает большая частота смешанного химериз-ма в Т-клеточной фракции среди пациентов с незло-качественными заболеваниями из-за использования у них менее интенсивных режимов кондиционирова-ния и, вероятно, отсутствия лимфодеплетирующих блоков химиотерапии до ТГСК.…”
Section: обсуждение результатов исследованияunclassified
“…В моно-и мультива-риантных анализах получено значимое влияние на риск ЦМВ-виремии, предшествующей острой РТПХ > II стадии, серопозитивности реципиента до ТГСК и наличия у пациента злокачественного заболевания. КВ ЭБВ-инфекции -33% (95% ДИ [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Фактором риска ЭБВ-виремии являлась острая РТПХ > II стадии.…”
unclassified